Novel recombinant adeno-associated viruses for Cre activated and inactivated transgene expression in neurons - Saunders, Arpiar; Johnson, Caroline; Sabatini, Bernardo (Frontiers in Neural Circuits, 2012)
Understanding the organization of the nervous system requires methods for dissecting the contributions of each component cell type to circuit function. One widely used approach combines genetic targeting of Cre recombinase to specific cell populations with infection of recombinant adeno-associated viruses (rAAVs) whose transgene expression is activated by Cre (“Cre-On”). Distinguishing how the Cre-expressing neurons differ functionally from neighboring Cre-negative neurons requires rAAVs that are inactivated by Cre (“Cre-Off”) and can be used in tandem with Cre-On viruses. Here we introduce two rAAV vectors that are inactivated by Cre and carry different fluorophore and optogenetic constructs. We demonstrate single and dual rAAV systems to achieve Cre-On and Cre-Off expression in spatially-intermingled cell populations of the striatum. Using these systems, we uncovered cryptic genomic interactions that occur between multiple Cre-sensitive rAAVs or between Cre-sensitive rAAVs and somatic Cre-conditional alleles and devised methods to avoid these interactions. Our data highlight both important experimental caveats associated with Cre-dependent rAAV use as well as opportunities for the development of improved rAAVs for gene delivery.